Formation of creativity of Ysmayil Boronchiev (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article talks about the creation of improvisation, its development and the creativity of famous Kyrgyz akyn Ysmayil Boronchiev. The development of Ysmayil Boronchiev’s creativity was influenced by a circle of creative people and meetings with creative people. The syncretic properties that provide oral singing of works of folk art, such as performance, melody and playing the komuz, are analyzed. Ysmail Boronchiev is known as a singer who followed traditional paths of creative development, studied and received education in accordance with the requirements of the era in which he lived, formed traditional themes, song construction techniques in his work.
Keywords: art, learning, attention, folk environment, memorization